Financial Leasing and its Impact on Small Enterprises in Palestine - Frehat, Aya Raed; Khalil, Amir Marzouq (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: This study aims to examine the nature of leasing contracts and their impact on the financing of small enterprises. It seeks to explore the rationale behind the reliance of small enterprises on leasing contracts by elucidating their characteristics, forms, associated risks, guarantees, and their implications on employment within these enterprises. Methods: The study employs a descriptive and analytical approach to examine the legislative provisions governing leasing contracts. It also delves into legal aspects of leasing within comparative legislation and considers relevant international frameworks, such as the Ottawa Convention on Leasing and the UNIDROIT Model Law on Leasing. Additionally, the study analyzes the value of leasing contracts by utilizing data published on the official website of the Palestinian Capital Market Authority. Results: The findings indicate that approximately 40% to 50% of leasing contracts pertain to small enterprises, reflecting a significant proportion. The study underscores the critical role of leasing in maintaining financial stability and sustaining employment levels within small enterprises, with a reported employment growth rate of 14.29%. Conclusions: The study concludes that leasing contracts are instrumental in the financing of small enterprises. It recommends incorporating provisions within Law No. (6) of 2014 that grant tax exemptions and relief from fees and taxes to small enterprises, thereby enhancing their financial viability.